Lingvistic and Didactic Approaches to Creation of Textbooks for Ukrainian Education in Diaspora - Romaniuk, Svitlana (Pedagogical Discourse, 2013)
The article deals with the creation of the basic principles of linguodidactic textbooks for teaching Ukrainian language in the system of native language schooling system of Western diaspora – primers and readers published. We analyze the procedure of learning letters and sounds, concluding texts primers based differentiation – for rural and urban students and in different seasons. Special attention is paid to the textbook which, in addition to literary texts should contain objectives of linguodidactic content aimed at mastering grammatical concepts and vocabulary enrichment system of language learners.